2015
DOI: 10.3174/ajnr.a4560
|View full text |Cite
|
Sign up to set email alerts
|

MR Elastography Demonstrates Increased Brain Stiffness in Normal Pressure Hydrocephalus

Abstract: Introduction Normal pressure hydrocephalus (NPH) is a reversible neurologic disorder characterized by a triad of cognitive impairment, gait abnormality and urinary incontinence that is commonly treated with ventriculoperitoneal shunt placement. However, there are multiple overlapping symptoms which often make it difficult to differentiate NPH from other types of dementia and improved diagnostic techniques would help patient management. MR elastography (MRE) is a novel diagnostic tool that could potentially ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 37 publications
(40 reference statements)
0
68
2
Order By: Relevance
“…15,36 The Streitberger protocol is based on three adjacent 6mm slices, which are subsequently integrated into two regions—global and periventricular—both of which were found to be less stiff in iNPH. By contrast, our protocol is driven by 3mm full-volume data sets segmented into anatomical regions using a warped lobar atlas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,36 The Streitberger protocol is based on three adjacent 6mm slices, which are subsequently integrated into two regions—global and periventricular—both of which were found to be less stiff in iNPH. By contrast, our protocol is driven by 3mm full-volume data sets segmented into anatomical regions using a warped lobar atlas.…”
Section: Discussionmentioning
confidence: 99%
“…Voxels with significant CSF contributions were masked to further ensure that recorded stiffness values accurately reflected changes in parenchymal tissue, rather than propagation of waveforms in spinal fluid spaces. 8,15–18 MRE image acquisition and processing protocols have been previously described. 16,17,19 , which we have previously demonstrated decreases variation in measurements of brain stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent work by Fattahi et al [32] instead found a slight increase in cerebrum stiffness of approximately 3.5% in 10 patients with NPH using MRE at 60 Hz. Here we report an extremely low brain stiffness of 1.62 kPa, which is approximately 46% lower than a normal brain stiffness of 3.0 kPa, and a much larger change in properties than previously reported for NPH.…”
Section: Discussionmentioning
confidence: 99%
“…MR elastography is a noninvasive study that evaluates the mechanical properties of tissue in vivo, and it has been shown in prior studies that pressure changes that cause changes in tissue elasticity can be detected by MR elastography [85,86] . Fattahi et al [84] reported their study of MR elastography in adult patients with normal pressure hydrocephalus, which showed that these patients had increased brain stiffness when compared with age-and sex-matched controls. These results suggest that MR elastography can perhaps serve as a novel diagnostic and surveillance tool in pediatric hydrocephalus.…”
Section: Experimental Imagingmentioning
confidence: 99%
“…Further developments are also being made in various advance MR techniques such as MR elastography for the assessment of brain and ventricular compliance or stiffness in patients with hydrocephalus [84] . MR elastography is a noninvasive study that evaluates the mechanical properties of tissue in vivo, and it has been shown in prior studies that pressure changes that cause changes in tissue elasticity can be detected by MR elastography [85,86] .…”
Section: Experimental Imagingmentioning
confidence: 99%